ISSUES PERTAINING TO DAAS - Umar, Muhammad; Akhtar, Tayyab Saeed; Osama, Muhammad (Journal of Ayub Medical College Abbottabad, 2017)
With the discovery of DAAs, the treatment of hepatitis C has improved a lot. But in this new era of DAAs several issues are also emerging. In this brief communication, we have tried to address the salient issues regarding DAAs. Keywords: Direct acting antivirals; Resistance; Drug Interactions; Side Effects